Oleate alters the immune response in non-small cell lung adenocarcinoma through regulation of HMGB1 release - Cole-Skinner, Breanna; Andre, Nicole M.; Blankenheim, Zachary; Root, Kate M.; Jafri, Kisa; Simmons, Glenn E. (Frontiers in Cell and Developmental Biology, 2024)
Cancer cell evasion of the immune response is critical to cancer development and metastases. The ability of clinicians to kickstart the immune system to target these rogue cells is an ever-growing area of research and medicine. In this study, we delved into the relationship between lipid metabolism, High Mobility Group Box 1 protein (HMGB1)-a pro-inflammatory damage-associated molecular pattern protein-and immune regulation within non-small cell lung adenocarcinoma (NSCLC). This allowed us to shed light on novel therapeutic avenues and potential personalized approaches for patients. We found that the expression of stearoyl CoA desaturase 1 (SCD1) was decreased in NSCLC tumors compared to normal tissues. This emphasized the critical role of lipid metabolism in tumor progression.Interestingly, monounsaturated fatty acid (MUFA) availability affected the expression of programmed death ligand-1 (PD-L1), a pivotal immune checkpoint target in lung cancer cells and immune cells, as well as HMGB1 suggesting a novel approach to modulating the immune response. This study uncovered a complex interplay between SCD1, PD-L1 and HMGB1, influencing the immunological sensitivity of tumors. Our work underscores the importance of understanding the intricate relationships between lipid metabolism and immune modulation to develop more effective NSCLC treatments and personalized therapies. As we continue to explore these connections, we hope to contribute to the ever-evolving field of cancer research, improving patient outcomes and advancing precision medicine in NSCLC.